Pengaruh Due Professional Care, Akuntabilitas, dan Kecerdasan Emosional Pada Kualitas Audit dengan Reward Sebagai Pemoderasi - Vidyantari, Putu Kemala; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p28, 2018)
This study aimed to get empirical evidence rewards as the moderating influence of due professional care, accountability, and emotional intelligence on audit quality. The sample is all the auditors who work in KAP province of Bali. The sampling method by using nonprobability sampling with saturated sample technique and the total is 47 auditor. Data was collected by questionnaire with survey technique and data analysis technique is Moderated Regression Analysis (MRA). The results of the analysis show that rewards strengthen the influence of due care professional, accountability, and emotional intelligence on audit quality. Ifdue care professional, accountability, and emotional intelligence increases then audit quality level gets higher and better with the supporteof reward. Keywords : Audit quality, due professional care, accountability, emotional  intelligence, reward